Fact Sheet Committee Draft of Vietnam War
This fact sheet outlines the Democratic Party's majority committee draft of the 1968 Vietnam platform plank. It commits the party to ending the war through an honorable and lasting negotiated settlement, rejecting escalation, unilateral withdrawal, or unconditional surrender, while supporting continued peace talks in Paris. The plank calls for an unconditional halt to the bombing of North Vietnam at a time that would not endanger U.S. troops and urges negotiations for a cease-fire and the withdrawal of all foreign forces from South Vietnam. It supports internationally safeguarded free elections in South Vietnam and emphasizes reducing U.S. military involvement by strengthening South Vietnamese forces while promoting economic and social reforms. Finally, it states that the United States seeks no permanent bases, military presence, or political role in South Vietnam, and that future U.S. assistance in Asia should be selective and based on mutual responsibility and regional cooperation.